The effect of angiotensin receptor blockers on peripheral artery disease progression: A retrospective cohort study in Jordan - Mahar Zaid Kasasbeh; Eilaf Mohammad Al-Rababˈah; Rawand A. Khasawneh; Fadi N. Asfar; Samah F. Al-Shatnawi; Nour A. Al-Sawalha (PLoS ONE, 2025)
Background Peripheral artery disease (PAD) is a common atherosclerotic vascular condition associated with many complications. The specific effect of angiotensin receptor blockers (ARBs) on the short-term complications in PAD patients has not been explored before. Objectives This study aimed to evaluate the association between ARBs use and the disease severity, progression, the frequency of surgical interventions, and arterial occlusion rates among users. Methods A retrospective cohort study was conducted at King Abdullah Ⅱ Hospital, including 133 patients followed between 2019 and 2024. The cohort was divided into two groups based on their exposure to ARBs: the ARBs group and the control group. Data related to patient demographics, clinical characteristics, medical history, laboratory results, vital signs, in addition to clinical outcomes were extracted from electronic medical records. Statistical analysis was performed using SPSS version 27.0. Results Among the participants, 24.8% experienced amputation, with 21.1% in the control group compared to 3.8% in the ARBs group. ARBs group has 79.2% lower Limb amputation (P-value 0.011; OR= 0.208, 95% CI 0.062–0.700) and 71% lower likelihood of having advanced PAD stage (stages III and IV) (P-value = 0.034, OR= 0.294, 95% CI = 0.095–0.911) compared to the control group. Linear regression analysis showed that the ARBs group has a decreased frequency of revascularization procedures (P-value 0.025;95% CI −1.004 – - 0.068). Conclusion ARBs may serve as a promising protective treatment option for PAD patients, potentially benefiting disease progression by lowering the risk of amputation and reducing the need for revascularization procedures.